INVENTARISASI JENIS POLEN PADA MELIPONIKULTUR Heterotrigona itama di KELURAHAN SUNGAI TIUNG, KOTA BANJARBARU - Nadia - Nurjannah; Anang Kadarsah; Sasi Gendro Sari (Jurnal Natural Scientiae, 2025)
The availability of food sources is very important for stingless bee farmers in Sungai Tiung Village, Banjarbaru City. Pollen is a food source that contains protein, vitamins, fats, and minerals that are important for bees. Pollen identification can be an indicator of the types of plants that bees feed on. This study aims to identify the types of pollen found in Heterotrigona itama nests and analyze each pollen category based on pollen percentage. The research was conducted at three different locations: Cempaka Kelulut, Cempaka Beton, and Kelulut Kalimantan. Samples were collected using purposive sampling. The acetolysis method was used as an indicator to identify pollen types. Pollen was identified by comparing and matching the observed characteristics with images or literature from identification guides, journals, and research theses. Based on the research results, the types of pollen found in Heterotrigona itama nests at the three meliponine beekeeping locations in Sungai Tiung Village were highly diverse. The pollen originated from 18 plant species and 13 plant families. Based on the percentage at Cempaka Beton, the dominant pollen is Scoparia dulcis (40%) and Phyllanthus urinaria (27.5%) as secondary pollen. At Cempaka Madu Kelulut, Phyllanthus urinaria is the predominant pollen (57%), while at Kelulut Kalimantan, Mimosa pudica dominates with (53.1%)